2020
DOI: 10.3390/antiox9040345
|View full text |Cite
|
Sign up to set email alerts
|

Inflamma-miR-21 Negatively Regulates Myogenesis during Ageing

Abstract: Ageing is associated with disrupted redox signalling and increased circulating inflammatory cytokines. Skeletal muscle homeostasis depends on the balance between muscle hypertrophy, atrophy and regeneration, however during ageing this balance is disrupted. The molecular pathways underlying the age-related decline in muscle regenerative potential remain elusive. microRNAs are conserved robust gene expression regulators in all tissues including skeletal muscle. Here, we studied satellite cells from adult and old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…miR-21 is one of the most studied miRs related to cellular senescence and inflammaging [ 18 , 40 ], and we found that it increased in EA and OA WT mice, whereas its expression did not change in NLRP3 − ones. As recently confirmed, miR-21 levels increased in senescent human umbilical vein endothelial cells (HUVECs) [ 41 ], in circulating extracellular vesicles of older people [ 41 ], as well as in plasma of older patients with frailty [ 17 ], whereas low miR-21 expression is related to health aging [ 18 ]. The pro-inflammatory effect of miR-21 may result from its ability to promote the NF-κB signaling pathway and subsequent NLRP3 inflammasome activation, acting directly on Toll-like receptors (TLRs) and/or through targeting A20 [ 15 ] ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…miR-21 is one of the most studied miRs related to cellular senescence and inflammaging [ 18 , 40 ], and we found that it increased in EA and OA WT mice, whereas its expression did not change in NLRP3 − ones. As recently confirmed, miR-21 levels increased in senescent human umbilical vein endothelial cells (HUVECs) [ 41 ], in circulating extracellular vesicles of older people [ 41 ], as well as in plasma of older patients with frailty [ 17 ], whereas low miR-21 expression is related to health aging [ 18 ]. The pro-inflammatory effect of miR-21 may result from its ability to promote the NF-κB signaling pathway and subsequent NLRP3 inflammasome activation, acting directly on Toll-like receptors (TLRs) and/or through targeting A20 [ 15 ] ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 96%
“…The pro-inflammatory effect of miR-21 may result from its ability to promote the NF-κB signaling pathway and subsequent NLRP3 inflammasome activation, acting directly on Toll-like receptors (TLRs) and/or through targeting A20 [ 15 ] ( Figure 8 ). Increased levels of proinflammatory cytokines, such as TNF-α and IL-6, as well as ROS, induced miR-21 expression in primary myoblast cultures, contributing to defective muscle regeneration and resulting in muscle atrophy [ 41 ]. The positive correlation between miR-21 expression and pro-caspase-1 and pro-IL-1β here measured, supports miR-21 relationship with age-dependent inflammation and muscle damage in WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the anti-apoptosis gene Bcl-2 and mitochondrial marker Nd-1 was also initially upregulated when miR-21 was inhibited. 117 In summary, miR-21 and miR-29 can promote cancer-associated sarcopenia, mainly by inducing cell apoptosis via TLR7/8 signaling.…”
Section: Cancer-derived Exosomal Micrornas In Sarcopeniamentioning
confidence: 98%
“…Inhibition of miR-21 in muscle satellite cells from elderly mice has been found to exert beneficial effects on myogenesis and could improve the decreased myotube size in vitro . 79 …”
Section: Ncrnas In Muscle Atrophy Induced By Agingmentioning
confidence: 99%